2007
DOI: 10.4049/jimmunol.178.7.4159
|View full text |Cite
|
Sign up to set email alerts
|

Minor Antigen H60-Mediated Aplastic Anemia Is Ameliorated by Immunosuppression and the Infusion of Regulatory T Cells

Abstract: Human bone marrow (BM) failure mediated by the immune system can be modeled in mice. In the present study, infusion of lymph node (LN) cells from C57BL/6 mice into C.B10-H2b/LilMcd (C.B10) recipients that are mismatched at multiple minor histocompatibility Ags, including the immunodominant Ag H60, produced fatal aplastic anemia. Declining blood counts correlated with marked expansion and activation of CD8 T cells specific for the immunodominant minor histocompatibility Ag H60. Infusion of LN cells from H60-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 48 publications
3
82
1
Order By: Relevance
“…25,26,34 At 10 days after LN injection, the proportion of IL-17A positive CD4 ϩ cells in B6 LN-cellinfused animals (15.0% Ϯ 1.1%) was significantly higher (P Ͻ .01) than that in TBI-only controls (6.5% Ϯ 1.3%). Almost no IL-17A positive CD4 ϩ cells were detectable in untreated animals ( Figure 4A upper panels).…”
Section: Dynamics Of Th1 and Th17 Immune Responses In A Mouse Model Omentioning
confidence: 99%
“…25,26,34 At 10 days after LN injection, the proportion of IL-17A positive CD4 ϩ cells in B6 LN-cellinfused animals (15.0% Ϯ 1.1%) was significantly higher (P Ͻ .01) than that in TBI-only controls (6.5% Ϯ 1.3%). Almost no IL-17A positive CD4 ϩ cells were detectable in untreated animals ( Figure 4A upper panels).…”
Section: Dynamics Of Th1 and Th17 Immune Responses In A Mouse Model Omentioning
confidence: 99%
“…Although numerous mechanisms have been proposed to explain the suppressive function of Tregs, none appears to be unifying, and the development of immunomodulating pharmacotherapies has been limited. 9 In mouse models, adoptive immunotherapy with Tregs has been shown to be effective in the prevention of experimental autoimmune encephalomyelitis, 10 type 1 diabetes, 11 SLE,12 autoimmune gastritis, 13 inflammatory bowel disease, 14 aplastic anemia, 15 graft rejection, 16 and GVHD. 17 It is likely that CD4 ϩ FOXP3 ϩ Tregs represent a mixture of thymic-derived and FOXP3 ϩ Tregs that are generated at peripheral sites.…”
Section: Introductionmentioning
confidence: 99%
“…According to the widely-accepted model of acquired aplastic anemia (AA), cytotoxic T lymphocytes (CTLs) recognize auto-antigens that are presented on hematopoietic stem cells (HSCs) through their class I human leukocyte antigen (HLA) molecules, playing an important role in initiation of the autoimmune reactions that lead to bone marrow (BM) failure [1][2][3]. Several indirect pieces of evidence have been reported in previous studies, such as the accumulation of T cells with particular clonotypes as demonstrated by T-cell receptor analyses [2,4,5], as well as the presence of T-cell clones capable of killing myeloid leukemia cell lines within the BM [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Several indirect pieces of evidence have been reported in previous studies, such as the accumulation of T cells with particular clonotypes as demonstrated by T-cell receptor analyses [2,4,5], as well as the presence of T-cell clones capable of killing myeloid leukemia cell lines within the BM [6,7]. However, it is entirely unknown what kind of cells the antigen-specific T cells attack and how these T cells diminish HSCs…”
Section: Introductionmentioning
confidence: 99%